2014
DOI: 10.1002/apj.1852
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the transformation behaviors of a Chinese coal ash using in‐/ex‐situ XRD and SEM‐EXD

Abstract: Crystal and phase transitions of a Chinese Datong coal ash were evaluated using room temperature X-ray diffraction (RT-XRD), in-situ high temperature (HT)-XRD, and scanning electron microscope combining energy dispersive X-ray analysis (SEM-EDX) as temperature varied from 300°C to 1600°C. The transforming behaviors of ash were related to its melting properties. Results revealed that the transforming behavior of minerals from in-situ HT-XRD was different with that from routine RT-XRD. Low-temperature Datong ash… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…28 Moreover, solid−liquid phase transformation could also be monitored by HT-XRD, enabling the detection on the fouling propensity induced by low-temperature eutectic. 29 Overall, the present study innovatively elucidated the original occurrences, especially the in situ transformation behavior and mechanism on the interactions among the corrosive substances during pyrolysis of Zhundong coal by combining the SSNMR, in situ HT-XRD and Factsagesimulation. The sequential removal of corrosive substances in high-basic coals and the strategic guidance on minimizing the fouling and slagging propensity during their utilization were proposed.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…28 Moreover, solid−liquid phase transformation could also be monitored by HT-XRD, enabling the detection on the fouling propensity induced by low-temperature eutectic. 29 Overall, the present study innovatively elucidated the original occurrences, especially the in situ transformation behavior and mechanism on the interactions among the corrosive substances during pyrolysis of Zhundong coal by combining the SSNMR, in situ HT-XRD and Factsagesimulation. The sequential removal of corrosive substances in high-basic coals and the strategic guidance on minimizing the fouling and slagging propensity during their utilization were proposed.…”
Section: Introductionmentioning
confidence: 88%
“…To some extent, in situ high-temperature X-ray diffraction (HT-XRD), an advanced analytical technique for characterizing inorganic matter in coal, could achieve the in situ analysis of minerals without recrystallization and decomposition of coal samples . Moreover, solid–liquid phase transformation could also be monitored by HT-XRD, enabling the detection on the fouling propensity induced by low-temperature eutectic …”
Section: Introductionmentioning
confidence: 99%
“…As a effective additive for removal of alkali metal, kaolin has been studied by many researchers on its removal mechanism. Partial kaolinite could be easily decomposed at a high temperature condition . And Linak’s research has proved that kaolin was excessive molten between 1373 and 1573 K during the burning processes, which lead to it inactivated and cannot continue to be used for further capture alkali metal.…”
Section: Introductionmentioning
confidence: 99%
“…Partial kaolinite could be easily decomposed at a high temperature condition. 8 And Linak's research 9 has proved that kaolin was excessive molten between 1373 and 1573 K during the burning processes, which lead to it inactivated and cannot continue to be used for further capture alkali metal. Gale also found that, when the temperature increased to 1573 K, the kaolin crystal structure would be collapsed 10 and the sintering phenomenon would also be occurred by the excessively melten of eutectics, both of which would sharply decrease the specific surface area and porosity of kaolin and lead to the deactivation of kaolin, so the adsorption capacity of kaolin for metal would be obviously reduced.…”
Section: Introductionmentioning
confidence: 99%
“…19 Therefore, it is of great significance to understand the influence of chemical composition and crystallization behavior on coal ash fusion mechanism and flow characteristics for the optimization design, stable operation, determination of operating parameters, and evaluation of coal adaptability in industrial gasification units. 20,21 The fluidity of coal ash slag is mainly determined by the chemical composition, atmosphere, and operating temperature during gasification. Coal ash is an extremely complex inorganic mixture composed of SiO 2 , A1 2 O 3 , Fe 2 O 3 , CaO, MgO, Na 2 O, K 2 O, TiO 2 , and other oxides.…”
Section: Introductionmentioning
confidence: 99%